A Dietary Plant Extract Formulation Helps Reduce Flea Populations in Cats: A Double-Blind Randomized Study - Damien Banuls; Jessie Brun; Jean-Louis Blua; Marie Christine Cadiergues (MDPI AG, 2023)
There is a growing demand for natural products to be used to control fleas in pets. A prospective, double-blind, randomized, placebo-controlled study evaluated the efficacy of the biological plant-based food supplement Bioticks® (thyme, rosemary, lemon balm, fenugreek, wormwood, and lemongrass extracts) as a flea control product in naturally flea-infested cats with an indoor-outdoor lifestyle. Ten cats were used as placebo controls (group A). Ten other cats were fed the same daily diet but supplemented with Bioticks® (group B). Fleas were counted by combing at D0 and D0 + 14 days, then one, two, three, four, and five months after the start of this study. No flea treatment was administered, and no environmental changes were made for six months prior to the start and throughout this study. The product was well-tolerated. The mean flea population in group B progressively and steadily decreased to reach 3.3 ± 2.1 at month five. At the same time and under similar maintenance conditions, the average flea population in group A remained stable (14.3 ± 2.5) until the fifth month. The percentages of efficacy (Abbott formula) in group B compared to group A was 27%, 20%, 52%, 66%, and 77%, respectively, at one, two, three, four, and five months after the start of this study.